2018
DOI: 10.32598/ptj.8.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning Effect of High-Intensity Aerobic Training on Myocardial Ischemia-Reperfusion Injury and Beclin-1 Gene Expression in Rats

Abstract: Purpose: Ischemia-Reperfusion (IR) injury is one of the most common cardiac disorders leading to irreversible heart damage. Many underlying mechanisms seem to be involved, among which disruption of cellular autophagy balance. Since physical training has a beneficial effect on the improvement of autophagy balance, it may have a cardioprotective effect against IR injury. This study investigates the protective role of aerobic training from cardiac IR injury and the autophagy process as a possible mechanism.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Moreover, two ( 2 ) studies reported an increased LC3II expression ( 27 , 31 ), while two other studies reported increased Beclin1 levels in IHD ( 27 , 32 ) as compared to normal controls. On the contrary, ET reversed these downregulated autophagosomal biomarkers in IHD ( 27 , 31 , 32 ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, two ( 2 ) studies reported an increased LC3II expression ( 27 , 31 ), while two other studies reported increased Beclin1 levels in IHD ( 27 , 32 ) as compared to normal controls. On the contrary, ET reversed these downregulated autophagosomal biomarkers in IHD ( 27 , 31 , 32 ).…”
Section: Resultsmentioning
confidence: 98%
“…As part of the essential mechanisms involved in the mitochondrial quality control, four studies ( 27 , 30 32 ) investigated the effect of IHD and ET on the mitophagy biomarkers ( Tables 2 , 4B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation